Stability of proposed biomarkers of prenatal androgen exposure over the menstrual cycle. (13th January 2015) - Barrett, E. S.; Parlett, L. E.; Swan, S. H.
Abstract : The prenatal hormonal milieu is widely believed to shape health later in life; however, there are considerable methodological challenges associated with measuring the in utero hormonal environment. Two potential biomarkers of prenatal androgen exposure that can be measured postnatally have been proposed: anogenital distance (AGD) and the ratio of the second to fourth digits of the hand (2D:4D). Although both measures are widely used research tools, their use in adult women may be complicated by the dramatic fluctuations in reproductive hormones across the menstrual cycle. To determine whether there is cyclical variation in these biomarkers, we conducted a longitudinal study of 12 naturally cycling, nulliparous adult women. Trained examiners assessed two measures of AGD [anus to clitoris (AGD-AC) and anus to fourchette (AGD-AF)] and 2D:4D in both hands for the duration of three menstrual cycles, taking measurements during the follicular, peri-ovulatory and luteal phases of each cycle. Despite the small sample size, longer (more masculine) AGD was associated with lower (more masculine) digit ratios, as predicted by the literature. Using multi-level linear regression models, we found that AGD and 2D:4D measurements did not differ significantly across cycle phases. AGD-AF and digit ratios in both hands were associated with age at menarche, suggesting a possible common developmental trajectory. These results demonstrate that AGD and 2D:4D are stable across the menstrual cycle. In addition, research is needed to determine how reliably these measures reflect the in utero hormonal milieu.